Relationship between Type of Antenatal Services and Delivery Outcomes in Denpasar, Bali - Ni Putu Sri Rahayu; Ni Wayan Ariyani; Gusti Ayu Marhaeni; Devi Syarief (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
The number of operative deliveries, especially sectio caesarea from 2013 to 2018 in Indonesia and Bali has increased and still exceeds the ideal limit. Prevention efforts are antenatal care according to standards that have developed accompanied by complementary care. The purpose of this study was to determine the relationship between the type of antenatal care and delivery outcomes in private midwife practice in Â Denpasar City Region. This type of research is correlation analysis using a cross sectional. The study was conducted in two different midwife practice in Denpasar in April â€“ May 2022. The research sample was 52 people. The sampling method with probability sampling technique is simple random sampling. Data analysis using Chi-square. There are 56% respondents who received integrated antenatal care and 96.3% respondents who received integrated antenatal care with complementary care gave birth spontaneously vaginally. There are 44% respondents who received integrated antenatal care and 3.7% respondents who received integrated antenatal care with complementary care. The results of the chi-square obtained a value of p 0.001 < 0,05. This result shows there is relationship between the type of antenatal care and delivery outcomes in PRIVATE MIDWIFE PRACTICE in the Denpasar City area. PRIVATE MIDWIFE PRACTICE is expected to develop integrated antenatal care accompanied by complementary midwifery care.Â